(untitled) (Veterinary Science, 2017)
In the present work was evaluated the effect of different parts of Prosopis flexuosa DC. var. flexuosa over the gastrointestinal activities of rats. In a complementary study were also assessed toxicity tests from aerial parts, bark and fruits, and increased dose-response essays of hydro-alcoholic extract of bark and aerial parts. The administration of aerial parts and bark increased the time of gastric emptying and reduce the intestinal motility when it was compare with the witness drug (hyoscin bromuro). Phyto-chemical studies of the bark showed present of the compound saponin, and tannins and flavonoids in aerial parts. As conclusion it was observed a toxicity effect in doses higher than 100 mg of the aerial parts, and an inhibitory effect doses-depended of the gastro-intestinal motility of steam and leaf of Prosopis flexuosa DC. var. flexuosa.